Intrauterine growth‐restricted pregnant rats, from placental ischemic dams, display preeclamptic‐like symptoms: A new rat model of preeclampsia - Jonna Smith; Madison Powell; Whitney Cromartie; Savanna Smith; Kylie Jones; Angie Castillo; Jordan Shaw; Joseph Editone III; Ahfiya Howard; Robert Tatum; Alex Smith; Brandon Fisher; et al. (Physiological Reports)
Abstract Preeclampsia (PE) is characterized by de novo hypertension (HTN) and is often associated with intrauterine growth restriction (IUGR). Hallmarks of PE are placental ischemia, decreased nitric oxide (NO) bioavailability, oxidative stress (OS), and organ damage in the kidneys and brain. This study aims to characterize a new model of PE using pregnant IUGR rats from hypertensive placental ischemic dams. It is hypothesized that pregnant IUGR rats from hypertensive placental ischemic dams will have elevated blood pressure (BP), OS, and organ damage. In this study, pregnant rats are divided into two groups: normal pregnant (NP) and hypertensive placental ischemic dams (RUPP). Offspring from NP and RUPP dams were mated at 10 weeks of age to generate pregnant IUGR (IUGR Preg) and pregnant control (CON Preg) rats. BP and other markers of PE were evaluated during late gestation. Pregnant IUGR rats had elevated BP and systemic OS. The maternal body weight of pregnant IUGR rats and their pups' weights were decreased, while the brains were enlarged with elevated OS. In summary, pregnant IUGR rats, born from hypertensive placental ischemic dams, have HTN and increased systemic and brain OS, with larger brain sizes and smaller pups. Furthermore, this study shows that pregnant IUGR rats exhibit a preeclamptic‐like phenotype, suggesting a new epigenetic model of PE.